A Multilayered Screening Method for the Identification of Regulatory Genes in Rice by Agronomic Traits. (January 2016) - Seol, Young-Joo; Won, So Youn; Shin, Younhee; Lee, Jong-Yeol; Chun, Jong-Sik; Kim, Yong-Kab; Kim, Chang-Kug
We developed a multilayered screening method that integrates both genome and transcriptome data to effectively identify regulatory genes in rice ( Oryza sativa ). We tested our method using eight rice accessions that differed in three important nutritional and agricultural traits, anthocyanin biosynthesis, amylose content, and heading date. In the genome resequencing of eight rice accessions with 24 RNA sequencing experiments, 98% of the preprocessed reads could be uniquely mapped to the reference genome, resulting in the identification of 42, 699 unique transcripts. Comparison between black and white rice cultivars showed evidence of intensive selective sweeps in chromosomes 3, 10, and 12. A total of 131 genes were differentially expressed among the black rice cultivars and found to be associated with three Gene Ontology terms (secondary metabolic process, biosynthetic process, and response to stimulus). We identified nonsynonymous Single Nucleotide Polymorphism (SNP) that likely play an important role in determining the agronomic traits differences, two upregulated and three downregulated genes in the black cultivars, and two downregulated genes in the white cultivars. The three agronomic traits were clearly grouped together by the developmental stages, regardless of any other traits, suggesting that the developmental stage is the most important factor that triggers global changes in gene expression. Interestingly, glutinous and nonglutinous black rice cultivars were distinguished from one another by different heading dates.